The Admonitions of Seh Bari - Drewes, G.W.J. (Asian Studies - Book Archive pre-2000., 1969)
New edition and complete translation of the sixteenth-century Javanese Muslim text "The Admonitions of Seh Bari". In his introduction, Drewes discusses the manuscript, script, spelling, punctuation, author, contents of the work, main ideas of the work, the Catechism drawn from this text, and a comparison of the Catechism with the main text.